2011
DOI: 10.3922/j.psns.2011.3.014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of psychoeducation in bipolar patients: Systematic review of randomized trials.

Abstract: Bipolar disorder is a recurrent and chronic disorder with significant morbidity and mortality. Currently, pharmacological treatment is considered indispensable in bipolar disorder. However, despite advances in this area, treatment remains suboptimal. A large body of research has shown that innumerable psychosocial factors influence the emergence of mood disorders. Therefore, in addition to pharmacological strategies, psychological interventions are increasingly recognized as an essential component in the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…1 and further discussion in ). It is therefore not surprising that studies included in recent reviews of psychoeducation for bipolar disorder have had considerable overlap with those in broader reviews of psychological therapies for relapse prevention .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 and further discussion in ). It is therefore not surprising that studies included in recent reviews of psychoeducation for bipolar disorder have had considerable overlap with those in broader reviews of psychological therapies for relapse prevention .…”
mentioning
confidence: 99%
“…These are education about the illness, the importance of regular routines and medication adherence, early detection of warning signs of relapse with strategies to prevent progression into full episodes, and enhancement of general coping strategies . Reviews of psychoeducation for bipolar disorder, while concluding that it is effective in preventing relapse , have commented that more evidence is needed that psychoeducation itself is effective, rather than as part of a multicomponent approach , and that the active ingredient and level of expertise needed for effective delivery are unclear .…”
mentioning
confidence: 99%
“…Family psychoeducation not only benefits the family but also the patient by reducing recurrence and violent behavior (Batista, Baes & Juruena, 2011;Harvey & O'Hanlon, 2013). Rahayu, Hamid, and Sabri (2011) reported that families who recieve family psychoeducation improve in their ability to provide psychosocial support to sick family members.…”
Section: Outputmentioning
confidence: 99%
“…Psychoeducation has been one of the most investigated psychotherapies [ 10 ] and is recommended by several guidelines as a first choice for the maintenance treatment of bipolar disorder [ 7 , 11 ]. Colom and colleagues reported the efficacy of 21-session group psychoeducation on relapse prevention in patients with bipolar II disorders in a randomized controlled trial [ 9 ].…”
Section: Introductionmentioning
confidence: 99%